High blood cholesterol in human might cause atheroskelerosis, a disease that eventually leads to the occurrence of coronary heart attack. This research was aimed to investigate level of sago waste or shrimp waste on plasma cholesterol and growth in rats. The experiment was conducted on 28 males Spraque dowley rat of one month old and was set up in a completely randomized design with seven treatments and four replications. The treatments were R0 (0 % sago waste and srimp meal) as a control, ASA 1 - Tabita N. Ralahalu; Kartiarso .; Aminuddin Parakkasi; Komang G. Wiryawan; Rudy Priyanto (Forum Pasca Sarjana, 2011)
High blood cholesterol in human might cause atheroskelerosis, a disease that eventually leads to the occurrence of coronary heart attack. This research was aimed to investigate level of sago waste or shrimp waste on plasma cholesterol and growth in rats. The experiment was conducted on 28 males Spraque dowley rat of one month old and was set up in a completely randomized design with seven treatments and four replications. The treatments were R0 (0 % sago waste and srimp meal) as a control, ASA 10 (10% of sago waste), ASA 20% (20% of sago waste), ASAF 10% (10% fermentation of sago waste), ASAF 20% (20% fermentation of sago waste), LU 10% (10% of srimp waste), LU 20% (20% of srimp waste). Variables measured included feed intake, body weight gain, plasma cholesterol, high density lipoprotein, low density lipoprotein, and triglyceride. The results showed that there was non-significant decrease in feed intake, whereas on body weight gain showed significant effect (P<0.05) between ASA 20%, ASAF 20% and LU 20%. Feed eficiency showed significant effect (P < 0, 01) between R0, ASA 20%, LU 10% with LU 20%. There was significant differences (P < 0.05) in plasma cholesterol between ASA 20% and R0, ASA 10%, LU 10% and 10% of ASAF, while HDL, LDL and plasma triglyceride did not indicate a significant effect between treatment. It is concluded that percentages of sago waste, fermentation of sago waste and shrimp waste in the ration as an effort to reduce cholesterol do not give a positive effect on feed intake, HDL, LDL and plasma triglyceride of rats; giving 20% of sago waste, 10% of fermentation of sago waste and 10% of shrimp waste showed significant effect on body weight gain, and the highest was obtained at a given ration ASA 20%, i.e. 3.55 g; giving ASA 20% has the highest feed eficiency that is 0.31; giving 20% of sago waste, fermentated sago waste and shrimp waste reduce cholesterol level significantly. The lowest plasma cholesterol was obtained at 20% ASA treatment that is 59.75 mg/dl. Key words: sago waste, fermentation, shrimp waste, rat performance